2012
DOI: 10.1007/s11626-012-9557-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and EGFP expression in the buffalo (Bubalus bubalis) mammary gland epithelial cell line

Abstract: This study was aimed to establish a buffalo mammary epithelial cells (BuMECs) line and maintain it for long-term by subculturing. BuMECs isolated from lactating buffalo mammary glands were cultured on a collagen matrix gel. BuMECs expressed significant amounts of the epithelial cell specific marker cytokeratin 18 as determined by immunohistochemistry. The BuMECs displayed monolayer, cobble-stone morphology, and formed lumen-, dome-, and duct-like structures. Furthermore, they were capable of synthesizing CSN2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…The RT-PCR results (Figure 12(A) and (B)) revealed the expression of all genes in isolated and cultured cells. Previous studies have also used the RT-PCR and Western blotting for the study of β-casein in cultured cells (Hu et al, 2009;Kaushik et al, 2013). Our Western blot results also showed the expression of β-casein in the cultured KHMESCs ( Figure 13).…”
Section: Karyotypingsupporting
confidence: 71%
See 3 more Smart Citations
“…The RT-PCR results (Figure 12(A) and (B)) revealed the expression of all genes in isolated and cultured cells. Previous studies have also used the RT-PCR and Western blotting for the study of β-casein in cultured cells (Hu et al, 2009;Kaushik et al, 2013). Our Western blot results also showed the expression of β-casein in the cultured KHMESCs ( Figure 13).…”
Section: Karyotypingsupporting
confidence: 71%
“…Earlier studies have also reported the expression of some of these genes in bovines (Hu et al, 2009;Kaushik et al, 2013;Monzani et al, 2011). BTN1A1 is a milk fat globule transmembrane glycoprotein and mammary-specific protein in milk fat secretion, which dominantly expressed on the mammary epithelial cells particularly during final stage of pregnancy and lactation (Fox & McSweeney, 2006;Szyda, & Komisarek, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delineation of mammary epithelial cell hierarchy, as perceived today, consists of MaSCs giving rise to uni-potent luminal-restricted progenitors that, in turn, differentiate into alveolar myoepithelial or secretory cells. According to recent studies, some in vitro and in vivo methods are currently being utilized to isolate, characterize and study stemness and progenitor activity of bovine putative mammary stem/progenitor cells, including morphology, histopathology 42, 56-59, bromodeoxyuridine retention 50, Hoechst dye-effluxing to identify side population (SP) properties and surface markers by flowcytometer or immunochemistry 23, 42.…”
Section: Mammary Gland Stem/progenitor Cellsmentioning
confidence: 99%